2013
DOI: 10.1371/journal.pone.0061376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Hedonic Appreciation of Pleasant and Unpleasant Odors

Abstract: Does hedonic appreciation evolve differently for pleasant odors and unpleasant odors during normal aging? To answer this question we combined psychophysics and electro-encephalographic recordings in young and old adults. A first study showed that pleasant odorants (but not unpleasant ones) were rated as less pleasant by old adults. A second study validated this decrease in hedonic appreciation for agreeable odors and further showed that smelling these odorants decreased beta event-related synchronization in ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…And indeed it actually is the case, since we showed that the relationship between pleasantness and sniffing behavior was conserved during normal aging (Experiment 4), even though the magnitude of the effect appeared, but not significantly, to be reduced. This is consistent with a recent study comparing young and old adults, in which sniffs were larger and longer for pleasant vs. unpleasant odors, independently of age (Joussain et al, 2013 ), and with studies in other modalities (e.g., face perception) showing that adaptive threat detection is unimpaired in older adults (Mather and Knight, 2006 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…And indeed it actually is the case, since we showed that the relationship between pleasantness and sniffing behavior was conserved during normal aging (Experiment 4), even though the magnitude of the effect appeared, but not significantly, to be reduced. This is consistent with a recent study comparing young and old adults, in which sniffs were larger and longer for pleasant vs. unpleasant odors, independently of age (Joussain et al, 2013 ), and with studies in other modalities (e.g., face perception) showing that adaptive threat detection is unimpaired in older adults (Mather and Knight, 2006 ).…”
Section: Discussionsupporting
confidence: 92%
“…For edibility, the weakness of the link can be explained by the fact that whether an odor comes from an edible source is not the sole criterion for determining whether it is relevant to the individual and for letting it reach the nasal mucosa without restriction (e.g., social odors are highly relevant despite being non-edible; Lundström et al, 2008 ). Edibility was more influential in the elderly than in younger adults, suggesting that this olfactory property may be processed differently in old age (as is hedonicity, for example: Joussain et al, 2013 ). For familiarity, a stronger link with sniffing was expected.…”
Section: Discussionmentioning
confidence: 99%
“…The general aim of the present study was to characterize olfactory function in ASD children at both the cognitive (odor familiarity and odor identification ability: objective 1 ) and sensorimotor and hedonic levels ( objective 2 ), by considering the positive and negative hedonic value of smells. To this end, a pleasant and an unpleasant odor (at various concentrations) selected from a previous study ( Joussain et al, 2013 ) were presented to ASD children and controls. The odors were embedded in a series of 16 stimuli including a non-odorized stimulus and odorant compounds that included both mixtures of molecules and their individual components.…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory psychophysical tasks most commonly measured in studies of olfaction in aging include odor identification, odor memory, odor discrimination and odor threshold sensitivity tasks [ 57 59 ]. Other methods which have been employed for clinical assessment of olfaction include surveys of subjective rating of olfactory ability and quality of life [ 60 ] and assessments of odor familiarity [ 61 ] and hedonics [ 62 ].…”
Section: Psychophysical Tasks Of Olfactionmentioning
confidence: 99%